2022
DOI: 10.3390/pathogens11060623
|View full text |Cite
|
Sign up to set email alerts
|

A Transfected Babesia bovis Parasite Line Expressing eGFP Is Able to Complete the Full Life Cycle of the Parasite in Mammalian and Tick Hosts

Abstract: Bovine babesiosis is caused by apicomplexan pathogens of the genus Babesia, including B. bovis. This protozoan parasite has a complex life cycle involving dynamic changes to its transcriptome during the transition between the invertebrate and vertebrate hosts. Studying the role of genes upregulated by tick stage parasites has been hindered by the lack of appropriate tools to study parasite gene products in the invertebrate host. Herein, we present tfBbo5480, a transfected B. bovis cell line, constitutively exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…At 30 days after Att-S74-T3Bo inoculation, vaccinated and control animals were challenged IV with one 1-ml stabilate containing 10 7 iRBC of the virulent homologous B. bovis strain Vir-S74-T3Bo. Previous studies have shown that a challenge dose of 10 7 iRBC of Vir-S74-T3Bo induces severe acute disease in calves with the onset of clinical signs starting approximately 9-10 days after infection ( 24 , 26 , 29 , 30 ). After challenge, all animals were monitored daily for clinical signs of acute bovine babesiosis, as described above.…”
Section: Methodsmentioning
confidence: 99%
“…At 30 days after Att-S74-T3Bo inoculation, vaccinated and control animals were challenged IV with one 1-ml stabilate containing 10 7 iRBC of the virulent homologous B. bovis strain Vir-S74-T3Bo. Previous studies have shown that a challenge dose of 10 7 iRBC of Vir-S74-T3Bo induces severe acute disease in calves with the onset of clinical signs starting approximately 9-10 days after infection ( 24 , 26 , 29 , 30 ). After challenge, all animals were monitored daily for clinical signs of acute bovine babesiosis, as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Following the genome sequencing of the B. bovis T2Bo strain (26), a marked increase in understanding the parasite's biology has emerged from functional studies using genetically modified parasites and high-throughput approaches (27)(28)(29)(30)(31)(32). Therefore, several novel parasite blood and tick stage antigens have been discovered and evaluated in vaccine trials (31,(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%
“…A transfected B. bovis line tfBbo5480 expressing eGFP [ 23 ] was used to generate sexual stages for immunofluorescence assay (IFA). Live B. bovis male and female-enriched gametes separated from induced sexual stage cultures were washed in PBS plus 3% bovine serum albumin (BSA).…”
Section: Methodsmentioning
confidence: 99%